Front Office Strategies To Promote Green Action Among Employees: A Case Study Of Marriott Hotels In Bali - Ruki, Made; Sadguna, I Gde Agus Jaya; Komala Sari, I Gusti Agung Mas Krisna (Ridwan Institute, 2025)
This study focuses at the strategies implemented by Bali Marriott Hotels' Front Office Department to encourage environmentally conscious actions among its employees. The research used a mixed-methods methodology over a six-month period in 2024, focusing on three luxury properties: The St. Regis Bali Resort, The Westin Resort Nusa Dua Bali, and The Laguna, A Luxury Collection Resort & Spa. The results show that front office staff members' environmental awareness as well as involvement were greatly increased by a variety of strategies that included comprehensive training, operational integration of green practices, employee recognition programs, cross-departmental collaboration, guest engagement, and innovative use of technology. According to the study, luxurious hotels may successfully implement sustainability programs without compromising the guest experience.